Early and enduring nutritional and functional results of pylorus preservation vs classic Whipple procedure for pancreatic cancer - Niedergethmann, Marco; Shang, Edward; Farag Soliman, Michael; Saar, Jochen; Berisha, Salih; Willeke, Frank; Post, Stefan (Langenbeck's archives of surgery, 2006)
Background and aims: There have been many supportive data that the pylorus-preserving pancreatoduodenectomy (PPPD) might be equal to the classic Whipple pancreatoduodenectomy (PD) in terms of oncological radicality. However, few reports are available on the early postoperative and enduring functional changes, nutritional status, body composition, and quality of life years after surgery. The aim of this study was to compare nutritional and functional results of the different techniques in a retrospective evaluation and prospective cohort study. Patients and methods: In May 1998, the standard surgical approach in the Department of Surgery, University-Hospital Mannheim, changed from PD to PPPD. The early postoperative and enduring functional changes, quality of life, oncological radicality, and nutritional status after years were compared between 128 patients after PD and 111 patients after PPPD. In a retrospective manner, the intra- and postoperative course was evaluated. In survivors, we prospectively analyzed the functional, nutritional, and oncological outcomes after 54 months (mean) in PD and after 24 months (mean) in PPPD patients. Results: The PPPD and PD groups did not differ according to age, gender, preoperative condition, or tumor localization. The PPPD group demonstrated favorable results (p<0.05) for operation time (PPPD 341±74 vs PD 386±89 min), blood loss (793±565 vs 1,000±590 ml), blood transfusions (416±691 vs 653±776 ml), delayed gastric emptying (6 vs 13%), and hospital stay (20 vs 24 days). However, a possible bias has to be mentioned since more T4 stages were diagnosed in the PD group (3 vs 11%), and even more extended (venous) resections were performed in the PD group (7 vs 24%). Morbidity (32 vs 30%) and mortality (5 vs 3%) did not differ between the two groups. After 24 months (PPPD, n=22) and 54 months (PD, n=16), there was no difference in global quality of life in recurrence-free patients. While the preoperative body weight was reached after 4 months (median) in the PPPD group, it was reached after 6 months (p<0.05) in the PD group. Bioelectrical impedance analysis (BIA) revealed a significantly (p<0.05) lower total body water (55 vs 60%) and significantly higher total body fat (26 vs 18%) in PPPD than in PD patients. Long-term follow-up showed no significant statistical differences in survival between both groups. Conclusion: Besides favorable postoperative outcome in specific aspects and equal oncological outcome of PPPD, pylorus preservation seems to have advantages in enduring functional and nutritional status years after surgery for pancreatic cancer.
Gesehen am 30.05.2022